Pengaruh Promosi dan Brand Image Terhadap Keputusan Pembelian Kopi Janji Jiwa Jilid 574 - Christianto, Bagas Rian; Astono, Anjar Dwi (UNIVERSITAS KALBIS, 2023)
This study aim to determine the effects of promotions, and brand image on purchase decision on Janji Jiwa Coffee Jilid 574. The method in this study is a quantitative method. Based on this study, researchers used quantitative data from the distribution of questionnaires. The sample in this study was 105 respondents with a non-probability sampling technique and purposive sampling method. The tests in this study include istrument validity tests and reliability tests, classical assumption tests, and hypothesis testing. the results of the t-test, it can be concluded that there is a significant influence of promotion and brand image on the purchasing decision on the Janji Jiwa Coffee Jilid 574. Based on the results of the F test, it can be concluded that Promotion and Brand Image jointly influence the purchase decision on the Janji Jiwa Coffee Jilid 574.